A meta-analysis of functional reading systems in typically developing and struggling readers across different alphabetic languages - Pollack, Courtney; Luk, Gigi; Christodoulou, Joanna A. (Frontiers in Psychology, 2015)
Functional neuroimaging research has identified multiple brain regions supporting reading-related activity in typical and atypical readers across different alphabetic languages. Previous meta-analyses performed on these functional magnetic resonance imaging findings typically report significant between-group contrasts comparing typical readers and readers with reading difficulty or a clinical diagnosis of developmental dyslexia. In order to advance our understanding of cross-linguistic convergence of reading-related brain activations for these reader groups, analyses using activation likelihood estimation were carried out separately for typical and atypical readers who ranged from children to adults. Contrasts were analyzed for tasks involving rhyming or reading of letter or word stimuli presented visually in English, Dutch, Italian, German, French, or Norwegian. Typical readers showed reliable activation in only left lateralized regions, including the inferior frontal area, precentral area and middle temporal gyrus. Atypical readers also showed activation in the left inferior frontal area and precentral region, in addition to significant activations in the right hemisphere, including the superior, medial and inferior frontal regions, lingual gyrus and the inferior occipital area. These results distinguish between typical and atypical reader group activations, showing common and distinct regions of activation when engaged in reading-related activities, extending previous meta-analyses on identifying brain regions relevant to reading to include cross-linguistic analyses for alphabetic scripts. Results support the universality of a signature pattern of brain activation in developmental dyslexia across alphabetic languages.